2016
DOI: 10.3319/tao.2016.03.02.01(tem)
|View full text |Cite
|
Sign up to set email alerts
|

1909 Taipei Earthquake Ground Motion Simulation

Abstract: The 1909 Taipei earthquake (M 7.3) occurred beneath the Taipei metropolitan area (TMA) causing substantial damage according to the historical literature. According to the hypocenter relocation and tectonic implications provided in a previous study, we simulated ground motions within the TMA using a hybrid simulation method involving the spectral-element method (SEM) and the empirical Green's function method (EGFM). We used the SEM for simulating low-frequency components and the EGFM for simulating high-frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Deterministic ground-motion prediction, prediction using earthquake scenario simulations, is attracting much research interest. To reliably simulate these scenarios requires comprehensive knowledge of fault models, especially knowledge of the geometry and slip heterogeneity of finite faults (Liao et al 2016;Wen et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Deterministic ground-motion prediction, prediction using earthquake scenario simulations, is attracting much research interest. To reliably simulate these scenarios requires comprehensive knowledge of fault models, especially knowledge of the geometry and slip heterogeneity of finite faults (Liao et al 2016;Wen et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that, despite the complex structure in eastern Taiwan, their hybrid approach successfully replicated the overall characteristics of broadband ground motion for the 2013 Ruisui earthquake. Liao et al (2016) performed a hybrid method comprising both the spectral-element and the empirical Green's function methods to simulate the ground motion of the 1909 Taipei earthquake. Their study indicated that the moment magnitude of the 1909 Taipei earthquake was either 7.3 with a stress drop of 30 bars, or between 6.8 and 7.3, but with a higher stress drop of > 100 bars.…”
mentioning
confidence: 99%